Violent Political Protest: Introducing a New Uppsala Conflict Data Program Data Set on Organized Violence, 1989-2019. (October 2022) - Svensson, Isak; Schaftenaar, Susanne; Allansson, Marie
This article presents the Uppsala Conflict Data Program (UCDP) "Violent Political Protest" (VPP) data set: a new –standalone- category of organized violence, which complements, and is compatible with, UCDP's three categories of organized violence: one-sided violence, non-state, and state-based conflict. It consists of violent political protests, with at least 25 casualties during a year, in which informally organized civilians challenge states over governmental or territorial issues. We describe the data collection process, and demonstrate the data's use with empirical analyses. Violent political protest is present globally, but most prevalent in the Middle East and Africa, and increasingly common over time. Violent political protest frequently co-occurs with state-based conflicts, but rarely due to conflict escalation. We explore if this is due to shared contexts, and find that gender inequality increases the likelihood of VPP onset, similar to state-based conflicts. Finally, we identify avenues for future research, including using VPP to assist in a more precise and complete analysis of organized violence.